A case of an omphalomesenteric duct remnant in an adult treated with laparoscopic surgery. (2015) - Morita, Keisuke; Haga, Yoshio; Miyanari, Nobutomo; Sawayama, Hiroshi; Matsumoto, Katsutaka; Mizumoto, Takao; Kubota, Tatsuo; Baba, Hideo
Highlights: An omphalomesenteric duct (OMD) remnant is a rare case in an adult. A ductal structure was found between the distal ileum and the umbilicus in this case. Laparoscopic surgery was performed by inserting three trocars into the left side of the abdomen. A good field of view around the umbilicus and adequate working space were provided. Both diagnosis and treatment were accomplished with minimally invasive laparoscopic surgery. Abstract: Introduction: The presence of an omphalomesenteric duct (OMD) remnant is a rare condition that typically affects the pediatric population. This report describes an extremely rare case of an OMD remnant that was diagnosed and resected by laparoscopic surgery in an adult. Presentation of case: A 52-year-old man underwent a medical examination at our hospital for right lower quadrant pain. Laboratory findings showed slight leukocytosis and an elevated C-reactive protein level. A luminal structure connected to the umbilicus was detected in the right pelvic wall by abdominal computed tomography, and an OMD remnant was suspected. Laparoscopic surgery was performed by inserting three trocars into the left side of the abdomen; no trocars were inserted near the umbilicus. This procedure provided both a good field of view around the umbilicus and adequate working space. We definitively diagnosed the structure as an OMD remnant and resected it with minimal invasion. The patient was discharged on postoperative day 7 without complications. Pathologic analysis found the lumen is covered by ileum-like mucosa, and a microabscess is formed in the surrounding fat tissue. Discussion: OMD remnants are uncommon, and their diagnosis is difficult. Most reports advocate for prompt surgical resection in symptomatic patients. Conclusion: In the present case, definitive diagnosis and treatment were accomplished with minimally invasive laparoscopic surgery.